The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.19184/ams.v3i3.5331
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Counseling on Group of First Thousand Days Of Life Effectively Improved Nutrition Awareness Knowledge and Attitude

Abstract: Nutrition status in the first thousand days of life (FTDL) of 270 days during pregnancy and 730 days in the infant's first life is a critical period, since the resulting consequences are permanent and irreparable. There are still many problems in the group of FTDL around the campus of University of Jember which require intensive handling, such as stunting, low energy protein, anemia, underweight and etc. Methods of improving the quality of nutrition for the FTDL group can be done by increasing knowledge about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
4
0
3
Order By: Relevance
“…Only a few respondents understood these facts. These results indicate that there were essential materials that were not yet known by mothers, thus, they need more education about nutrition (Marchianti et al, 2017). The results of the statistical analysis showed that there was a significant relationship between maternal knowledge and nutritional status (p = 0.01 for stunting and p=0.04 for undernutrition by Spearman rho test) with a weak relationship (coefficient correlation = 0.12 and 0.10).…”
Section: Maternal Eating Behavior's Knowledgementioning
confidence: 92%
See 1 more Smart Citation
“…Only a few respondents understood these facts. These results indicate that there were essential materials that were not yet known by mothers, thus, they need more education about nutrition (Marchianti et al, 2017). The results of the statistical analysis showed that there was a significant relationship between maternal knowledge and nutritional status (p = 0.01 for stunting and p=0.04 for undernutrition by Spearman rho test) with a weak relationship (coefficient correlation = 0.12 and 0.10).…”
Section: Maternal Eating Behavior's Knowledgementioning
confidence: 92%
“…For instance, several agricultural areas which are very fertile and have abundant food sources apparently have a high rate of malnutrition in children (Beal et al, 2018). The ability of families to optimally utilize existing potential sources to meet the nutritional needs of children under five shows that the contribution of appropriate technology training to increase knowledge, attitude and practice for low-income residents is a necessity, especially to overcome the problem of under-nutrition in children under five (Marchianti, Sakinah, & Diniyah, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Status gizi ketika kehamilan berkaitan dengan stunting karena ketika masa kehamilan termasuk 1000 hari pertama kehidupan dimana sangat menjadi penentu kesehatan dan status gizi anak.3 Ibu hamil yang status gizinya kurang atau menderita kekurangan energi kronik (KEK) berdasarkan perhitungan dan pengukuran lingkar lengan atas maka berpotensi melahirkan anak yang prematur dan cenderung akan stunting. 15 Hasil analisis statistik menggunakan uji chi square menunjukkan bahwa ada pengaruh yang signifikan antara status gizi kehamilan dengan stunting pasca pandemi Covid-19 di Kabupaten Balangan (p = 0,002). Hasil penelitian ini relevan dengan penelitian lain bahwa ada pengaruh yang signifikan antara status gizi ketika hamil dengan stunting, apabila ibu menderita KEK ketika hamil maka akan berdampak melahirkan anak yang kekurangan gizi seperti stunting.…”
Section: Pembahasan 1 Status Gizi Kehamilanunclassified
“…Based on cases of occupational diseases in Indonesia, the incidence in East Java in 2010 reached 107.4 million people. Based on previous research on workers, the risk factors for worker posture reached 15%, work at 18%, and work duration at 58% (Marchianti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%